Influence of Involvement, Institutional Affiliation, and Geographic Location on Membership Retention in Voluntary Professional Organizations - Judith McIntosh White (Journal of Applied Communications, 2005)
The reasons people join voluntary professional organizations and continue membership is largely an unexplored area of research. This study sought to find some answers in membership data from the Association for Communication Excellence in Agriculture, Natural Resources, and Life and Human Sciences (ACE) from 1991 to 2004. Descriptive statistics, bivariate correlations, and, in some cases, simple linear regression were calculated for a variety of variables for 1,441 valid records. The findings suggest that a relationship exists between organization involvement and members’ identification with and sense of commitment to ACE, leading to continued membership. Findings also suggest that geography makes no difference in member retention. Results were unclear concerning the impact of employer affiliation on continued membership. Further research into individual member characteristics and the collection of more data are recommended.